Opportunities and challenges for TCR mimic antibodies in cancer therapy. (2nd August 2016) - Chang, Aaron Y.; Gejman, Ron S.; Brea, Elliott J.; Oh, Claire Y.; Mathias, Melissa D.; Pankov, Dmitry; Casey, Emily; Dao, Tao; Scheinberg, David A.
ABSTRACT: Introduction : Monoclonal antibodies (mAbs) are potent cancer therapeutic agents, but exclusively recognize cell-surface targets whereas most cancer-associated proteins are found intracellularly. Hence, potential cancer therapy targets such as over expressed self-proteins, activated oncogenes, mutated tumor suppressors, and translocated gene products are not accessible to traditional mAb therapy. An emerging approach to target these epitopes is the use of TCR mimic mAbs (TCRm) that recognize epitopes similar to those of T cell receptors (TCR). Areas covered : TCRm antigens are composed of a linear peptide sequence derived from degraded proteins and presented in the context of cell-surface MHC molecules. We discuss how the nature of the TCRm epitopes provides both advantages (absolute tumor specificity and access to a new universe of important targets) and disadvantages (low density, MHC restriction, MHC down-regulation, and cross-reactive linear epitopes) to conventional mAb therapy. We will also discuss potential solutions to these obstacles. Expert o pinion : TCRm combine the specificity of TCR recognition with the potency, pharmacologic properties, and versatility of mAbs. The structure and presentation of a TCRm epitope has important consequences related to the choice of targets, mAb design, available peptides and MHC subtype restrictions, possible cross-reactivity, and therapeutic activity.